2021
DOI: 10.1038/s43246-021-00130-5
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial strain-induced phase transition in the 2D topological semimetal IrTe2

Abstract: Strain is ubiquitous in solid-state materials, but despite its fundamental importance and technological relevance, leveraging externally applied strain to gain control over material properties is still in its infancy. In particular, strain control over the diverse phase transitions and topological states in two-dimensional transition metal dichalcogenides remains an open challenge. Here, we exploit uniaxial strain to stabilize the long-debated structural ground state of the 2D topological semimetal IrTe2, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…Secondly, inverted band gaps of the bulk electronic structure are obtained as well. These inverted band gaps are expected to result in topological surface states and resonances 9 , which indeed appears to be consistent with a very recent ARPES-study 10 .…”
Section: Density Functional Theorysupporting
confidence: 90%
See 1 more Smart Citation
“…Secondly, inverted band gaps of the bulk electronic structure are obtained as well. These inverted band gaps are expected to result in topological surface states and resonances 9 , which indeed appears to be consistent with a very recent ARPES-study 10 .…”
Section: Density Functional Theorysupporting
confidence: 90%
“…Fig. 1 (a,b)) IrTe 2 exhibits bulk Dirac points, spin-orbit driven gap inver-sions and the corresponding topological surface states, which all emerge from the Te 5p derived bands [9][10][11][12] . It is particularly exciting that this system not only hosts a topological electronic band structure but also superconductivity below 3 K, raising great hopes for intrinsic topological superconductivity [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…In the (5×1) phase, 5 atoms split in 2 dimerized Ir atoms represented with light blue bullets (one dimer) and 3 undimerized atoms [Figure 3 (a) & Figure 1 (cd)]. This leads to a splitting of the Ir 4f 7/2 core level into a contribution due to the dimerized Ir atoms [6,32,14,27], at higher binding energy, and a contribution due to the 3 undimerized Ir atoms. These different contributions in XPS are used to acquire XPD diffractograms specific to the local environment of the monomer (undimerised) and dimer Ir atoms.…”
Section: X-ray Photoemission Spectroscopymentioning
confidence: 99%
“…A second phase transition occurs at T c 2 = 180 K, characterized by a bulk (8 × 1 × 8) superstructure. This has stimulated numerous scanning tunneling microscopy (STM) [22,15,6,18,23] and angle-resolved photoemission spectroscopy (ARPES) studies [14,24,25,26,6,27], which revealed additional periodicities and a surface periodicity (6 × 1) appearing after a third phase transition at T c 3 = 165 K. These surface-sensitive probes disclosed a complex evolution of the electronic structure of IrTe 2 through its phase transitions that calls for state-of-the-art ab-initio calculations for a better understanding. This requires the determination of the atomic structure of IrTe 2 in the different reconstructed phases up to a few atomic layers below the surface, to be comparable to the probing depth of typical ARPES measurements.…”
Section: Introductionmentioning
confidence: 99%
“…1b) to triclinic structure (P 1) around 280 K, accompanied by complex stripe phase 20 with periods of (3n+2)×1×(3n+2) (n = 1,2,3,...) in the bulk 20,21 and (3n+2)×1 on the surface 22,23 . Recent scanning tunnelling microscopy and ARPES study on strained IrTe 2 shows 6×1 phase can be stabilized by strain 24 . Suppressing the stripe phase by doping or intercalation 20,25 leads to emergence of superconductivity.…”
Section: Introductionmentioning
confidence: 99%